2016
DOI: 10.15439/2016f529
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Affective Intervention Process in Development of Affect-aware Educational Video Games

Abstract: Abstract-In this paper initial experiences are presented on implementing specific methodology of affective intervention design (AFFINT) for development of affect-aware educational video games. In the described experiment, 10 student teams are to develop affect-aware educational video games using AFFINT to formalize the whole process. Although all projects are still in progress, first observations and conclusions may already be presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Extreme arousal levels, both high and low, are associated with higher location variance and transition time, which means more frequent movement as compared to the neutral state. In the case of high arousal, the patterns of movement locations, measured with circadian movement (6), are more regular [83].…”
Section: Feature Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Extreme arousal levels, both high and low, are associated with higher location variance and transition time, which means more frequent movement as compared to the neutral state. In the case of high arousal, the patterns of movement locations, measured with circadian movement (6), are more regular [83].…”
Section: Feature Evaluationmentioning
confidence: 99%
“…In recent years, there has been increasing interest in the automatic recognition of emotions and taking into account the emotional state of a person in various applications in many fields. Solutions implementing the automated recognition of emotions are used, among others, in marketing, systems monitoring driver tiredness, e-learning, healthcare, education [6], entertainment [7,8], software engineering [9,10], etc. Many different approaches to emotion recognition have been developed, which use more and more advanced algorithms achieving increasing effectiveness.…”
Section: Emotion Recognitionmentioning
confidence: 99%
“…Research has also shown that children who play educational video games could improve their skills more easily compared to those who did not play educational video games [14].…”
Section: Background On Serious Gamesmentioning
confidence: 99%